A high temperature and high pressure synthesis method of cerium nitrogen compound

The synthesis of cerium nitrogen compounds under high pressure through diamond anvil technology and infrared laser heating has solved the problem of insufficient pressure relief stability of polymerized nitrogen compounds, and achieved the normal pressure unloading and high energy content characteristics of cerium nitrogen compounds C2/mCeN3. Broaden its application scenarios.

CN119018860BActive Publication Date: 2025-01-10JILIN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411534367.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-10
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

In the prior art, the polymerized nitrogen compounds prepared under high pressure are insufficient in the process of pressure relief, which limits their practical application under normal pressure. There are few reports on the high-pressure synthesis of cerium nitrogen compounds and the improvement of stability, which affects the Its application scenarios are broadened and the synthesis of other polymeric nitrogen compounds are synthesized.

Method used

Diamond-to-anvil technology combined with infrared laser heating, metal cerium or cerium nitride reacts with nitrogen at a high pressure of 21.4 GPa to 25.3 GPa to generate cerium nitrogen compound CeN3 with N2 and N4 units, and passes through liquid nitrogen as a transfer. Press the medium and reactants to control the synthesis conditions to improve the stability of the product.

Benefits of technology

The cerium nitrogen compound C2/mCeN3 generated under high pressure was successfully synthesized and can be unloaded to normal pressure conditions, showing high energy content characteristics, suitable for energy storage, and provides ideas to improve pressure relief stability and broaden application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119018860B_ABST
    Figure CN119018860B_ABST
Patent Text Reader

Abstract

The invention discloses a high-temperature and high-pressure synthesis method of a cerium nitrogen compound, which belongs to the technical field of high-temperature and high-pressure synthesis of special application materials. First, pre-pressing, drilling and resetting are performed in a diamond anvil; after pressing metal cerium or cerium nitride into thin slices with a large anvil press in a nitrogen glove box with a water and oxygen content of less than 0.01 ppm, the sample slices are pierced by a sample needle, and the sample is picked up with the sample needle tip and placed in an experimental press; the entire experimental press is immersed in liquid nitrogen, the pressure screw is rotated, and liquid nitrogen is loaded into the experimental press, and the experimental press containing metal cerium and nitrogen or cerium nitride and nitrogen is pressurized to 21.4 GPa~25.3 GPa by a diamond anvil device, and heated to 2600~3000K by an infrared laser, and maintained for 30 seconds to obtain a cerium nitrogen compound CeN3. The product synthesized by the invention is a high-energy substance that can be applied to the field of energy storage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of high-temperature and high-pressure synthesis of special application materials, and specifically relates to a high-temperature and high-pressure synthesis method of a cerium nitrogen compound. Background Art

[0002] High temperature and high pressure technology is a common technical means to prepare new materials. Intense high temperature and high pressure reactions are taking place all the time inside the earth. By combining diamond anvil cell technology with laser heating technology, new polymer synthesis research can be carried out through chemical reactions under high pressure. Most polymerized nitrogen compounds prepared under high pressure have excellent properties, such as high energy density, high bulk modulus and exotic electronic properties. However, the pressure relief stability of some polymers limits their practical applications under normal pressure.

[0003] Cerium is the element with the highest content among the rare earth elements in the earth's crust. It has a large atomic radius and rich valence states. Its strong chemical pre-compression effect can reduce the synthesis pressure, and its multivalent state provides a rich chemical environment for stabilizing the polymerized nitrogen structure. In experimental and theoretical work, cerium has shown a certain ability to combine with nitrogen. In experimental studies, metallic cerium can react chemically with nitrogen to form cerium nitride (CeN) at normal pressure. The existence of cerium nitride (CeN) at normal pressure also provides a new precursor for the synthesis of new polymerized nitrogen structures under high pressure. At 30 engineering atmospheres, metallic cerium is nitrided to generate La 2 O 3 CeN 2 In this compound, nitrogen exists in the form of ions; when researchers heated metal cerium immersed in nitrogen at 30 GPa and 2000 K, the diffraction pattern changed significantly, but they failed to successfully identify the specific product. In the theoretical prediction research work under high pressure, some cerium nitrogen compounds containing polymerized nitrogen structures that can be unloaded to normal pressure conditions have emerged. For example: dumbbell-shaped N 2 and N 4 CeN molecular chain 3 , containing four helical CeN 4 , with N 14 Layered structure of CeN rings 6 However, so far, there have been few reports on the high-pressure synthesis and identification of cerium nitrogen compounds containing polymeric nitrogen structures, as well as attempts to use different reactant precursors to improve the stability of the products during pressure relief. This is very necessary to enrich people's understanding of the structure of cerium nitrogen compounds under high pressure, improve the stability of high-pressure synthesized polymeric nitrogen compounds under normal pressure, thereby broadening their application scenarios, and provide new ideas for the synthesis and stability of other related polymeric nitrogen compounds. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the background technology and provide a high-temperature and high-pressure synthesis method of cerium nitrogen compounds.

[0005] The technical solution adopted by the present invention is as follows:

[0006] A high-temperature and high-pressure synthesis method for cerium nitrogen compounds comprises the following steps: firstly, preparing an experimental device: pre-pressing, drilling and resetting in a diamond anvil; pressing metal cerium or cerium nitride into thin slices by a large anvil press in a nitrogen glove box with a water and oxygen content of less than 0.01 ppm, then piercing the sample slices with a sample needle, picking up the sample with the sample needle tip and putting it into an experimental press; immersing the entire experimental press in liquid nitrogen, rotating a pressure screw, loading liquid nitrogen into the experimental press, nitrogen acting as a pressure transmission medium and also as a reactant to participate in the synthesis reaction under high temperature and high pressure, pressurizing the experimental press containing metal cerium and nitrogen or cerium nitride and nitrogen to 21.4 GPa~25.3 GPa by using a diamond anvil device, heating to 2600~3000K by using an infrared laser, and maintaining for 30 seconds, thereby obtaining a cerium nitrogen compound CeN 3 .

[0007] As a preferred method, during the experiment, cerium nitride and nitrogen are pressurized to 21.4 GPa and heated to 3000K to finally obtain a cerium nitrogen compound that can be maintained at normal pressure. C 2 / m C 3 .

[0008] Preferably, the laser used for heating during the experiment is an infrared laser with a wavelength of 1064 nanometers and a full power output of 100 W.

[0009] Preferably, the gaskets used in the experiment are all T301 steel sheets.

[0010] Preferably, during the experiment, the experimental standard pressure mode of metal cerium and nitrogen is the change of R1 line of ruby ​​fluorescence with pressure, and the experimental standard pressure mode of cerium nitride and nitrogen is the change of the first-order Raman peak of diamond with pressure. Beneficial Effects

[0011] The present invention successfully synthesized N by laser heating cerium nitride and nitrogen under high pressure. 2 and N 4 The cerium nitride compound with a polymeric nitrogen structure of 21.4 GPa and 3000 K was generated. C 2 / m C 3 Can be unloaded to normal pressure conditions. C 2 / m C 3 The detonation pressure and detonation velocity are: Pd =25.68 GPa, V d =5.95 Km / s, is a high-energy substance and can be used in the field of energy storage. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 The figure is a comparison of the Raman spectra of metal cerium and nitrogen in Example 1 before and after laser heating at 25.3 GPa.

[0013] Figure 2 The figure is a comparison of the X-ray diffraction spectra of metal cerium and nitrogen in Example 1 before and after laser heating at 25.3 GPa.

[0014] Figure 3 The product of implementation example 1 P -1 CeN 3 Refinement of the X-ray diffraction spectrum at synthesis pressure of 25.3 GPa.

[0015] Figure 4 The product of implementation example 1 P -1 CeN 3 Pressure relief Raman spectrum.

[0016] Figure 5 The product of implementation example 1 P -1 CeN 3 Decompression X-ray diffraction spectrum.

[0017] Figure 6 This is a comparison of Raman spectra of cerium nitride and nitrogen in Example 2 before and after laser heating at 21.4 GPa.

[0018] Figure 7 This is a comparison of X-ray diffraction spectra of cerium nitride and nitrogen in Example 2 before and after laser heating at 21.4 GPa.

[0019] Figure 8 The product of implementation example 2 C 2 / m C 3 Refinement of the X-ray diffraction spectrum at synthesis pressure 21.4 GPa.

[0020] Fig. 9 The product of implementation example 2 C 2 / m C 3 Pressure relief Raman spectrum.

[0021] Fig.10 The product of implementation example 2 C 2 / m C 3 Decompression X-ray diffraction spectrum.

[0022] Fig.11 The product of implementation example 2 C 2 / m C 3 The X-ray diffraction spectrum was refined at atmospheric pressure.

[0023] Fig.12 Prepared in Example 1 P -1 CeN 3 Schematic diagram of the structure.

[0024] Fig.13 Prepared in Example 2 C 2 / m C 3 Schematic diagram of the structure. DETAILED DESCRIPTION Example 1

[0025] A diamond anvil with an anvil surface of 300 microns was selected to generate high pressure, and a T301 steel sheet was used as a gasket material. The diamond anvil was pre-pressed on the steel sheet to produce an indentation. A laser puncher punched a circular hole with a diameter of 150 microns in the center of the indentation as a sample cavity, and a ruby ​​was placed in it as a standard pressure material. In a glove box filled with argon gas and with water and oxygen content below 0.01 PPm, the 0.25 mm thick surface protective layer of metal cerium was scraped off, and the cerium foil was cut into pieces with a scalpel. After the diamond with an anvil surface of 500 microns in diameter was pressed into a thin sheet, it was pierced with a sample needle, and metal cerium was selected and loaded into the sample cavity. After that, the press was immersed in liquid nitrogen, and the pressure nut of the diamond anvil was rotated to load liquid nitrogen into the press. After the pressure increases, nitrogen will phase change into a solid and act as a pressure transmission medium and also as a reactant to participate in the subsequent chemical reaction. The experimental press equipped with cerium nitride and nitrogen was heated by a laser with a wavelength of 1064 nanometers and a full power output of 100 W. During the experiment, Raman spectrometer, X-ray diffractometer and synchrotron radiation source were used to characterize the process before and after laser heating and the pressure relief process. After laser heating, the XRD test results were used to identify the structure of the product, and the Raman test results were used to analyze the Raman vibration of the product. The stability of the product was characterized based on the changes in the pressure relief Raman and pressure relief X-ray diffraction signals with pressure relief. Figure 1 This is a Raman test image of metal cerium and nitrogen before and after laser heating at 25.3 GPa and 2600 K. 184 cm -1 、294 cm -1 and 418 cm -1 The Raman vibration mode at 1105 cm corresponds to the lattice vibration of nitrogen before laser heating. After heating at 25 GPa and 2600 K, the lattice vibration peak and molecular peak of nitrogen almost completely disappear. -1New Raman modes emerge, which are different from those of pure Ce or pure N in CeN. 2 The results showed that the laser heating process did not correspond to any known phase, indicating that during the laser heating process, cerium and nitrogen reacted to form a new cerium nitrogen compound. In order to further confirm the phase changes before and after laser heating and to identify the specific products, an X-ray diffraction experiment was conducted. In the subsequent X-ray diffraction test, a diamond anvil with an anvil surface of 300 microns was selected to generate high pressure, and a T301 steel sheet was used as the gasket material. Figure 2 The significant change in the peak signal observed before and after heating is clearly illustrated in the X-ray diffraction patterns before and after laser heating. Figure 2 As shown, through Ce metal and ε-N 2 The combination of the X-ray diffraction pattern before laser heating can be identified. Figure 3 The structure of the product after laser heating at 25.3 GPa was compared with the theoretical prediction, and the diffraction pattern was fitted by Le Bail, confirming that these new peaks correspond to P- 1Structure of CeN 3 phase. And Figure 1 The 1105 cm -1 The Raman peak at P -1 CeN 3 The vibration mode between the nitrogen-nitrogen single bond and the nitrogen-nitrogen double bond in the P -1 CeN 3 After the addition of the compounds, the DAC was carefully depressurized and Raman and XRD measurements were performed at each step of depressurization to track possible changes. Figure 4 The Raman pressure relief signal changes with pressure. P -1 CeN 3 It starts to decompose at about 8.5 GPa and is sensitive to the test laser. Figure 5 P -1 CeN 3 It can also be seen from the decompression X-ray diffraction spectrum that when the pressure is released to 8.6 GPa, the P -1 CeN 3 The main peak also weakened, which also means P -1 CeN 3 Under the conditions of 25.3 GPa and 2600 K, laser heating of metal cerium and nitrogen produced a new 2 and N 4 Unit P -1 CeN 3 ; however, the compound cannot be unloaded to atmospheric conditions.

[0026] Example 2

[0027] A diamond anvil with an anvil surface of 300 microns was selected to generate high pressure, and a T301 steel sheet was used as a gasket material. The diamond anvil was pre-pressed on the steel sheet to produce an indentation, and a laser puncher punched a circular hole with a diameter of 150 microns in the center of the indentation as a sample cavity. In a glove box filled with nitrogen and with water and oxygen content less than 0.01 PPm, the cerium nitride powder was pressed into a thin sheet on a diamond anvil surface with a diameter of 500 microns, and then crushed with a sample needle, and a cerium nitride sheet of appropriate size was selected and loaded into the sample cavity. After that, the press was immersed in liquid nitrogen, and the pressure nut of the diamond anvil was rotated to load liquid nitrogen into the press. After the pressure increases, nitrogen will phase change into a solid as a pressure transmission medium and also as a reactant to participate in the subsequent chemical reaction. The experimental press equipped with cerium nitride and nitrogen was carried out using a diamond anvil device, and laser heating was performed using a laser with a wavelength of 1064 nanometers and a full power output of 100 W. During the experiment, Raman spectrometer, X-ray diffractometer and synchrotron radiation source were used to characterize the product before and after laser heating and during the pressure relief process. After laser heating, the XRD test results were used to identify the structure of the product, and the Raman test results were used to perform Raman vibration analysis of the product. The stability of the product was characterized based on the changes in the pressure relief Raman and pressure relief X-ray diffraction signals with pressure relief. Figure 6 This is a comparison of the Raman spectra of cerium nitride and nitrogen before and after laser heating at 21.4 GPa and 3000K. It can be seen that at 1085 cm -1 A new Raman peak appears at P-1 C 3 In order to confirm the specific product after laser heating, the present application conducted an X-ray diffraction test. Figure 7 The X-ray diffraction patterns at 21.4 GPa before and after laser heating are shown. In the figure, only B1 phase CeN and ε-N were observed before laser heating. 2 , many new diffraction peaks appeared after laser heating, accompanied by incompletely reacted B1-type CeN. Figure 3 The structure of the product after laser heating at 25.3 GPa was compared with the theoretical prediction, and the diffraction pattern was fitted by Le Bail, confirming that these new peaks correspond to C 2 / m Structure CeN 3 phase. And combined Figure 6 After laser heating at 1085 cm -1 The Raman peak at Figure 1 The 1100 cm -1 The Raman peaks nearby are very similar, both with the two CeN 3 There are similar structural units and the length of the nitrogen-nitrogen bond is very consistent. C 2 / m C 3After the addition of the compounds, the DAC was carefully depressurized and Raman and XRD measurements were performed at each step of depressurization to track possible changes. Fig. 9 The Raman decompression signal changes with pressure. C 2 / m C 3 Can be depressurized to normal pressure. Fig.10 C 2 / m C 3 The decompression X-ray diffraction spectrum also shows that C 2 / m C 3 The main peak can be traced back to normal pressure conditions. Fig.11 is the X-ray diffraction pattern at normal pressure and C 2 / m C 3 The fitting comparison further confirmed that C 2 / m C 3 Under the conditions of 21.4 GPa and 3000 K, laser heating of cerium nitride and nitrogen produced P -1CeN 3 Also has N 2 and N 4 Unit C 2 / m C 3 ; however, the compound can be unloaded to atmospheric conditions.

[0028] In summary, the present invention pressurizes the cerium nitrogen mixture to above 20 GPa and further prepares two high-purity CeN by laser heating. 3 , comparing two different CeN 3 It can be seen from the synthesis path and pressure relief stability of the compound that the present invention proposes that when selecting a synthetic precursor CeN with high symmetry and relatively higher stability under high pressure, the yield of the product CeN can be effectively improved. 3 The symmetry and pressure relief stability of the polymerized nitrogen structure provide an effective solution for the synthesis of other polymerized nitrogen structures and the improvement of pressure relief stability, and the C 2 / m C 3 It can be used as a potential energetic material.

Claims

1. A high-temperature and high-pressure synthesis method for cerium nitrogen compounds, comprising the following steps: first, preparing an experimental device: pre-pressing, drilling, and resetting in a diamond anvil; pressing metal cerium or cerium nitride into thin slices using a large anvil press in a nitrogen glove box with a water and oxygen content of less than 0.01 ppm, then piercing the sample slices with a sample needle, picking up the sample with the sample needle tip and placing it in an experimental press; immersing the entire experimental press in liquid nitrogen, rotating the pressure screw, and loading liquid nitrogen into the experimental press. Nitrogen acts as a pressure transmission medium and also as a reactant to participate in the synthesis reaction under high temperature and high pressure. The experimental press containing metal cerium and nitrogen or cerium nitride and nitrogen is pressurized to 21.4 GPa~25.3 GPa using a diamond anvil device, and heated to 2600~3000K using an infrared laser, and maintained for 30 seconds to obtain a cerium nitrogen compound CeN3.

2. The high temperature and high pressure synthesis method of a cerium nitrogen compound according to claim 1, characterized in that: During the experiment, cerium nitride and nitrogen were pressurized to 21.4GPa and heated to 3000K, and finally a cerium nitrogen compound that can be maintained at normal pressure was obtained. C 2 / m CeN3.

3. The high temperature and high pressure synthesis method of a cerium nitrogen compound according to claim 1, characterized in that: The laser used for heating during the experiment is an infrared laser with a wavelength of 1064 nanometers and a full power output of 100 W.

4. The high temperature and high pressure synthesis method of a cerium nitrogen compound according to claim 1, characterized in that: The gaskets used in the experiment were all T301 steel sheets.

5. The high temperature and high pressure synthesis method of a cerium nitrogen compound according to claim 1, characterized in that: During the experiment, the experimental standard pressure method for metallic cerium and nitrogen was the change of the R1 line of ruby ​​fluorescence with pressure, and the standard pressure method for cerium nitride and nitrogen experiments was the change of the first-order Raman peak of diamond with pressure.